2019 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2019
DOI: 10.1109/iros40897.2019.8967704
|View full text |Cite
|
Sign up to set email alerts
|

SuMa++: Efficient LiDAR-based Semantic SLAM

Abstract: Reliable and accurate localization and mapping are key components of most autonomous systems. Besides geometric information about the mapped environment, the semantics plays an important role to enable intelligent navigation behaviors. In most realistic environments, this task is particularly complicated due to dynamics caused by moving objects, which can corrupt the mapping step or derail localization. In this paper, we propose an extension of a recently published surfelbased mapping approach exploiting three… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
192
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 378 publications
(222 citation statements)
references
References 39 publications
(51 reference statements)
2
192
0
Order By: Relevance
“…The mapping trajectory is compared with two types of previous approaches; Basic LiDAR SLAM without semantic information, Semantic mapping without the explicit model of uncertainty. More specifically, LOAM [ 16 ] is adopted for the basic LiDAR SLAM, and SuMa++ [ 7 ] is selected for the comparison with the semantic mapping only when the RangeNet++ is used for the semantic segmentation algorithm. Figure 16 shows the trajectory evaluation results using KITTI datasets.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mapping trajectory is compared with two types of previous approaches; Basic LiDAR SLAM without semantic information, Semantic mapping without the explicit model of uncertainty. More specifically, LOAM [ 16 ] is adopted for the basic LiDAR SLAM, and SuMa++ [ 7 ] is selected for the comparison with the semantic mapping only when the RangeNet++ is used for the semantic segmentation algorithm. Figure 16 shows the trajectory evaluation results using KITTI datasets.…”
Section: Methodsmentioning
confidence: 99%
“…In [ 39 ], Semantic LOAM (SLOAM) was proposed for forest inventory using an end-to-end pipeline for tree diameter estimation. Furthermore, SuMa++ presented semantic ICP and dynamic filtering using the semantic information from RangeNet++ for semantic mapping [ 7 ]. These studies showed the technological breakthrough in the semantic mapping field, however, the uncertainty from the semantic segmentation algorithms was not explicitly considered.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the fact that depth information is not considered, one significant difference from our approach is that this work uses 2D bounding boxes to represent the objects. Other innovative approaches have focused on point-wise semantic labeling for 3D lidar data within the SLAM framework itself [11]. This work also highlights urban scenarios for autonomous driving as an important application area.…”
Section: Related Workmentioning
confidence: 98%
“…Most semantic SLAM methods fuse semantic labels obtained from semantic segmentation and maps generated by the SLAM algorithm to generate 3D maps with semantic information. According to the type of sensor they used, semantic SLAM algorithms can be classified as the monocular camerabased [17]- [19], stereo camera-based [20], [21], LiDARbased [22]- [24], multiple sensors-based [25], [26], RGB-D camera-based approaches, and so on. This paper mainly considers semantic SLAM algorithms based on the RGB-D camera.…”
Section: Semantic Slammentioning
confidence: 99%